2008
DOI: 10.1039/b714950f
|View full text |Cite
|
Sign up to set email alerts
|

Shape-dependent plasmon resonances of gold nanoparticles

Abstract: Localized surface plasmon resonances in noble metal nanoparticles cause enhanced optical absorption and scattering that is tunable through the visible and near-infrared. Furthermore, these resonances create large local electric field enhancements at the nanoparticle surfaces, essentially focussing light at the nanometer scale. These properties suggest a range of applications, including biomedical imaging, therapeutics, and molecular sensing. Here we review some recent advances regarding shape-dependent optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
328
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 447 publications
(341 citation statements)
references
References 82 publications
8
328
0
5
Order By: Relevance
“…It is consistent with the previous reports that the longitudinal band of GNRs is more sensitive to the local environment around GNRs than the transverse band [42][43][44][45]. This result suggested that the aggregation of GNRs takes place in a side-by-side manner [46,47].…”
Section: +supporting
confidence: 82%
“…It is consistent with the previous reports that the longitudinal band of GNRs is more sensitive to the local environment around GNRs than the transverse band [42][43][44][45]. This result suggested that the aggregation of GNRs takes place in a side-by-side manner [46,47].…”
Section: +supporting
confidence: 82%
“…In these methods the metal ions are reduced but need thermal treatment. 9 In this paper, we report precise dopoing of gold nanoparticles in borate matrix, viz. "lithium-borate rubyglass-ceramics" without thermal treatment and addition of any reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, urchin-like or branched gold particles with a rough surface are of great significance. The high surface area endows them excellent performance in catalysis, surface plasmon resonance (SPR) [7], surface-enhanced Raman spectra (SERS) [8], electronic devices, and biological applications [1,2,9].In particular, owing to the existence of a large electromagnetic field enhancement at the tips of branched particles, a strong SERS activity can be detected with intensity over 10 7 and a relatively high reproducibility [8]. In addition, the urchin-like structure leads to large SPR shift from 500 to 800 nm and tunable SPR enhancement light scattering and absorption, making them novel and highly effective contrast agents for in vivo cancer diagnosis and therapy [10].…”
Section: Introductionmentioning
confidence: 99%